2012
DOI: 10.1111/j.1365-2648.2012.06034.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ competence in genetics: a mixed method systematic review

Abstract: There is little evidence on this topic, but it does appear from the available evidence that nurses are not demonstrating the competences needed to offer holistic health care to people with genetic conditions. Pre- and post-registration programmes must be enhanced to include genetic health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 30 publications
(106 reference statements)
6
68
0
5
Order By: Relevance
“…As shown in Figure 2, the majority of study respondents have still to adopt. This reflects the findings and comments of many authors in this field on the need for nurses to engage with genetics (Burton 2011, Task & Finish Group 2011, Skirton et al 2012.…”
Section: Discussionsupporting
confidence: 71%
“…As shown in Figure 2, the majority of study respondents have still to adopt. This reflects the findings and comments of many authors in this field on the need for nurses to engage with genetics (Burton 2011, Task & Finish Group 2011, Skirton et al 2012.…”
Section: Discussionsupporting
confidence: 71%
“…The findings that knowledge, involvement and confidence relating to genetics and nutritional genomics are limited among dietitians mirror results of studies conducted with other non-genetic health professionals such as physicians, nurses, midwives and allied health professionals (Metcalfe et al 2002;Skirton et al 2012;Godino and Skirton 2012;Benjamin et al 2009;Lapham et al 2000;Long et al 2001). Efforts to increase the awareness and competence of health professionals in relation to genetics and genomics have been addressed via multiple approaches.…”
Section: Preparedness Of Health Professionalsmentioning
confidence: 83%
“…[22] A systematic review of literature to establish the scope of nursing practice attaining these core competencies revealed that nurses are not demonstrating the skills to appropriately provide care to people with genetic conditions. [39] Faculty are still uncomfortable with this subject content and are inadequately preparing their students. [5,22] Assessment of comfort level, as shown in Table 5, revealed only one aspect that the majority of participants were comfortable in, which was requesting more education about genetic conditions, with 19 NEs, 8 RNs and 2 DNPs very comfortable with this request.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses' overall confidence and comfort in performing genetic-genomic related tasks is relatively low. [39] Understanding educational training confirms the need for more inclusion of genetic-genomic content into curriculum and the need to further educate nurse faculty. …”
Section: Participantsmentioning
confidence: 99%